Correlation between the hemoglobin-to-hematocrit ratio and 3-month outcomes in patients with acute ischemic stroke: a secondary analysis based on a prospective cohort study - Liu, Dulin; Liu, Hongjuan; Li, Yanling; Zhou, Quan; Huang, Zhihua (Frontiers in Neurology, 2025)
BackgroundOur study dedicated to clarify the connection between the hemoglobin (HB) to hematocrit (HCT) (HB/HCT) ratio and adverse outcomes (AOs) in patients with acute ischemic stroke (AIS) within 3 months.MethodsA total of 1,906 individuals with AIS were encompassed at a hospital in South Korea. A binary logistic regression model (BLRM) was utilized to explore the linear relationship between the HB/HCT ratio and AOs in patients with AIS. Additionally, generalized additive models (GAMs) and smooth curve fitting were leveraged to investigate the nonlinear relationship between the HB/HCT ratio and AOs in patients with AIS. Two steps recursive method was adopted to calculate the inflection point.ResultsThere was a nonlinear relationship between the HB/HCT ratio (per 0.01) and AOs in AIS patients according to the GAMS score and smooth curve fitting. The inflection point of the HB/HCT ratio (per 0.01) is 33.191. On the left side of the inflection point, the risk of AOs decreased by 27.80% for every 1 unit increase in the HB/HCT ratio (per 0.01) (odds ratio (OR) = 0.722, 95% confidence interval (CI): 0.577, 0.903, p = 0.004). On the right side of the inflection point, the risk of AOs increased by 20.90% for every 1 unit increase in the HB/HCT ratio (per 0.01) (OR = 1.209, 95% CI: 1.014, 1.440, p = 0.034).ConclusionOur study revealed a U-shaped relationship between the HB/HCT ratio and the prognosis of AIS. Monitoring HB/HCT ratio may be able to identify patients with AOs in advance, ultimately providing more reference of scientific and effective care for AIS patients which may be linked to the improvement of their clinical outcomes.